Influence of state of health and personality factors of resilience and coping in healthy subjects and those with diabetes - Rivera-Picón, Cristina; Benavente-Cuesta, María Hinojal; Quevedo-Aguado, María Paz; Juárez-Vela, Raúl; Martinez-Tofe, Jesús; Sánchez-González, Juan Luis; Rodríguez-Muñoz, Pedro Manuel (Frontiers in Public Health, 2023)
The diagnosis of Diabetes Mellitus requires modification in lifestyle, which requires a great capacity for adaptation and modification of habits. The aim of the study was to determine whether personality factors and health status influence resilience and coping strategies in a sample of healthy and diabetic subjects. These samples were selected following a quota sample at the University Hospital of Salamanca. The study participants were 200 healthy subjects and 201 patients with diabetes. The total sample consisted of 401 subjects. The results show that certain personality factors, such as emotional stability, conscientiousness, integrity and extraversion, were positively related to resilience. Additionally, emotional stability, integrity and extraversion were positively associated with rational coping. On the other hand, emotional stability, agreeableness and extraversion were negatively related to emotional coping. In relation to health status, the absence of pathology is related to the use of rational strategies more than to the diagnosis of diabetes. Therefore, the participants in this study present different psychological patterns depending on personality and health status.